Has the time for a European job guarantee policy arrived? - Rania Antonopoulos (Levy Economics Institute of Bard College, 2023)
As country after country in the European Union is called to respond to the current challenge of our time - high inflation and declining real wages - governments must engage in a transformative agenda and go beyond emergency energy vouchers and income support cashtransfers. And if the goal is to lead the way to a resilient and sustainable European Union, business as usual will not do. The share of wages to GDP has been declining since the late 1970s, deregulation of labor markets has increased insecurity and precariousness, and, among ordinary working people, a sense of uncertainty, disenfranchisement, and mistrust in governing institutions is prevalent. A thorough re-evaluation of policies is needed. In response to the deterioration of living standards, a guarantee of minimum wages adequate to secure a decent living standard should be a starting point; a permanent policy of automatic adjustment of wages to inflation rates in all member states should be promoted; and strengthening collective bargaining agreements ought to be re-invigorated for a fair sharing of productivity between wages and profits. An EU Job Guarantee should be at the center of this policy transformation. This bold agenda, advocated in this paper, can mobilize people to regain trust that a Social Europe is possible.
Keywords: B5; D6; E24; E61; E62; H1; H3; H4; H5; J2; J3; J4; J16; 330; Inflation; Job Guarantee; Social Europe; Income Distribution